The role of posttraumatic stress and posttraumatic growth on online information use in breast cancer survivors. Issue 8 (25th May 2018) - Casellas‐Grau, A.; Sumalla, E.C.; Lleras, M.; Vives, J.; Sirgo, A.; León, C.; Rodríguez, A.; Campos, G.; Valverde, Y.; Borràs, J.M.; Ochoa, C.
Abstract: Objective: Changes perceived as both positive (eg, posttraumatic growth [PTG]) and negative (eg, posttraumatic stress symptoms [PTSS]) have been associated with intensive Internet use among breast cancer survivors. In this multicenter study, we analyzed the role of PTG and PTSS on the amount of time spent looking for online cancer information, its content, and its psychological impact. Methods: Posttraumatic stress symptoms and PTG were assessed in 182 breast cancer survivors by using the Post‐traumatic Stress Disorder Checklist and Post‐traumatic Growth Inventory questionnaires. Subjects also completed a questionnaire about their behavior when looking for online illness‐related information (ie, time spent, type of contents, and psychological impact). Results: Posttraumatic stress symptoms positively correlated with the amount of time spent looking for cancer‐related information, including both medical and psychosocial content. By contrast, PTG showed no relationships with the amount of time, but with a predominant search for cancer‐related psychosocial information. The psychological impact of online information was associated with participants' levels of PTG and/or PTSS. Whereas PTG was related to a decrease of women's hope, PTSS was linked to the perception of being less conscious or inadequately informed about the illness, thereby increasing feelings of distress. Conclusions: Posttraumatic stress symptoms and PTG show relationships with the amount of time spent online, the type of information accessed online, and the psychological impact of Internet use. Health professionals should prescribe online information according to the psychological response to cancer. There is a need for professional‐led online resources to provide patients with timely information as well as support sites to facilitate psychological adjustment.